Abstract Book: Interdisciplinary Innovation in Drug Development: Challenges and Opportunities for Indonesia - Molecular Probes Discovery Group (Pharmaceutical Reports, 2025)
It is a great pleasure and honor for me, on behalf of the organizing committee, to welcome you to the International Conference on Interdisciplinary Innovation in Drug Development: Challenges and Opportunities for Indonesia. We are truly delighted to host this important gathering of scientists, professionals, and scholars in the field of pharmaceutical sciences and drug discovery. This conference aims to serve as a dynamic platform for the exchange of ideas, research findings, and collaboration opportunities across disciplines, with a focus on the innovation and transformation of drug development, especially in response to global health challenges. I would like to express our deepest appreciation to Prof. Kazuma Ogawa from Kanazawa University, Japan for his gracious presence here with us today. We are truly honored by his participation, and we look forward to his insightful presentation. Our sincere thanks also go to all our invited speakers from various institutions who are joining us virtually:Prof. Bambang Purwono, Ph.D. (Universitas Gadjah Mada, Yogyakarta)Prof. apt. Muchtaridi, Ph.D. (Universitas Padjajaran, Bandung)Assoc. Prof. apt. Muammar Fawwaz, Ph.D. (Universitas Muslim Indonesia, Makassar)Dr. rer.nat. Rien Ritawidya, M.Farm (National Research Center, BRIN, Serpong.Though distance separates us physically, your knowledge and contributions are invaluable and help to enrich the depth and scope of this conference. We also extend our heartfelt gratitude to all participants, sponsors, reviewers, moderators, and the organizing team who have worked tirelessly to make this event a success. Total participants are 160 participants divided into offline 75, and online 85 participants.